Different Parameters Influencing to Extraction and Drying of Anthocyanin Powder from Magenta (Peristrophe Roxburghiana) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
Leaves of magenta (Peristrophe roxburghiana) have a good source of anthocyanin. They have potential health benefits for human consumption. Objective of the present study to examine various aspects affecting to anthocyanin extraction including blanching, solvent, solvent: solid, extraction time and temperature under ultrasound, carrier and temperature for drying. Optimal results were clearly shown that the panda leaves should be blanched under 95oC in 10 seconds; extraction should be conducted by ethanol 90%, ethanol: solid (2.0:1.0), 60oC, 8 minutes; vaccum drying should be executed at 60oC with the support of carrier (0.5 maltodextrin: 0.5 gelatin: 1.0 magenta fluid). Ultrasonic had positive effect on anthocyanin extraction and this method could be utilized to optain the most anthocyanin powder.Keywords: Magenta, Anthocyanin, Ultrasonic, Blanching, Solvent, Extraction, Carrier, Drying.